1979
DOI: 10.1002/lary.5540891003
|View full text |Cite
|
Sign up to set email alerts
|

Paranasal sinus aspergillosis

Abstract: Four cases of aspergillosis of the paranasal sinuses seen recently at the North Carolina Baptist Hospital are reported. Paranasal sinus aspergillosis is prone to develop in patients living in the southeastern states because those states 1. have an agricultural economy and 2. have a hot, humid climate that causes a high incidence of nasal and sinus disorders. The increasing use of immunosuppressive and oncological drugs should further increase the incidence of aspergillosis. Diagnosis of aspergillosis of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 15 publications
0
28
0
1
Order By: Relevance
“…A significantly higher incidence is reported in restricted areas that have warm and dry climate . [9,23,24] Its incidence in recent years has shown marked increase specially in north Sudan, in southwestern states of USA and in north India. Rhinosinusitis is a common disorder affecting approximately 20% of the population at some time of their lives.…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher incidence is reported in restricted areas that have warm and dry climate . [9,23,24] Its incidence in recent years has shown marked increase specially in north Sudan, in southwestern states of USA and in north India. Rhinosinusitis is a common disorder affecting approximately 20% of the population at some time of their lives.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relation between fungal infection and tumor formation is not understood. Several studies have shown that aspergillus infection can cause aspergilloma formation at various sites [2][3][4][5][6][7] , and some studies have described bronchogenic carcinoma caused by pulmonary aspergilloma 6 , whilst others have described only the coexistence of aspergilloma and carcinoma in the same cavity 5,7 . Although it is not understood how aspergillosis could induce carcinoma formation, the chronic inflammation caused by prolonged fungal infection might be carcinogenic.…”
Section: ⅲ Discussionmentioning
confidence: 99%
“…Immunocompromised patients are at particular risk for fulminant invasive aspergillosis. The most frequent site of human aspergillus infection is the lung, followed by the liver, spleen, bone, meninges, and paranasal sinuses 2 . In several reports, the coexistence of fungal infection and malignancy has been noted in the brain and thoracic cavity [3][4][5][6] .…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…Environmental factors which might explain the epidemiology of fungal sinusitis are the agricultural economy, which encourages proliferation of the Aspergillus organism, and the warm, moist climate with its attendant high rate of allergic and infectious rhinosinusitis. 2 Genetic predisposition might also play a role in the pathogenesis of this disease. Immunosuppressive conditions such as chemotherapy, immunosuppressive therapy and congenital conditions such as Fanconi's or aplastic anemia might also predispose to fungal sinusitis, as seen on some of our patients with fulminant fungal sinusitis.…”
Section: Discussionmentioning
confidence: 99%